Selectivity of essential oils to the egg parasitoid Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) - Ewerton Santos Sombra, Kassio (Revista Ciência Agronômica, 2021)
The diversity of arthropod pests has required the combined use of various control methods. The application of essential oilsshowing insecticidal, repellent or phage-inhibiting activity, together with the release of natural enemies, can improve integrated pest managementprovided the oils display selectivity. The aim of this study was to evaluate the selectivity of the oils of rosemary pepper [Lippia origanoidesKunth (Verbenaceae)], citronella [Cymbopogon winterianus Jowitt. (Poaceae)] and lemongrass [C. citratus (DC) Stapf.] for Trichogrammapretiosum Riley (Hymenoptera: Trichogrammatidae), comparing fi ve concentrations (0.01, 0.05, 0.1, 0.5 and 1.0%), and a control (neutraldetergent at 1.0%). Residual toxicity was evaluated using adult mortality, calculating lethal concentrations (LC50) in addition to the reductionsin parasitism in eggs of Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) and selectivity for the par asitoids. The three oils showedselectivity for the parasitoid T. pretiosum, resulting in a mortality rate of between 17.2% (rosemary pepper) and 32.2% (lemongrass) at thelowest concentration. The essential oil of rosemary pepper stood out with an LC50 of 0.43%, a reduction of only 22% in parasitism(Class 1 - Innocuous) and 88.0% emergence, at a dose of 0.01%. The LC50 of the lemongrass oil was 0.15%, with a 34.0% reductionin parasitism (Class 2 - Slightly harmful) and 74.0% emerged adults. For the citronella oil, the LC50 was 0.12%, with a reductionof 46.0% (Class 2 - Slightly harmful) and emergence of 62.0%. The selectivity of the essential oils makes possible to release T.pretiosum, integrating biological control with botanical insecticides, as long as non-sprayed eggs are parasitised by T. pretiosum.